1983
DOI: 10.1071/pp9830237
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Properties of Developing Bean and Pea Leaves

Abstract: The rate of O2 uptake in the dark in bean leaves and leaf slices decreased during development. The use of inhibitors of the cytochrome and alternative pathways and the uncoupier carbonyl cyanide p-trifluoromethoxyphenylhydrazone (FCCP) indicated that this decline was largely due to a decline in the activity and capacity of the cytochrome path. However, the capacity of the alternative path remained more or less constant with leaf expansion, and thus percentage cyanide resistance of respiration increased with le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
27
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 0 publications
7
27
2
Order By: Relevance
“…Furthermore, when mature leaves were studied, the amounts of mtNDPK were found to be very low, probably an indication of lower mitochondrial activity or mitochondrial number. These results are in agreement with previous work showing that the levels of respiratory capacity and efficiency of oxidative phosphorylation decreases with aging in pea leaves (Azcó n- Bieto et al, 1983).…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, when mature leaves were studied, the amounts of mtNDPK were found to be very low, probably an indication of lower mitochondrial activity or mitochondrial number. These results are in agreement with previous work showing that the levels of respiratory capacity and efficiency of oxidative phosphorylation decreases with aging in pea leaves (Azcó n- Bieto et al, 1983).…”
Section: Discussionsupporting
confidence: 83%
“…The rate of respiratory CO2 release in the dark of attached adult leaves was measured at 21°C at the end of the night period, using the same Li-Cor gas exchange system. 02 uptake rates of leaf slices (1-2 mm thick) in the dark were measured at the end of the night period using an 02 electrode (Rank Brothers, Cambridge, England) as previously described (7,8). The use of respiratory inhibitors (potassium cyanide and salicylhydroxamic acid) and uncouplers for estimating the activity of mitochondrial electron transport pathways in vivo was described earlier (7,8).…”
Section: Gas Exchange Measurementsmentioning
confidence: 99%
“…The substrate used was vermiculite. Plants were watered every day, and nutrients were given two or three times a week with full-strength Hewitt solution (7). Photosynthetic (17).…”
mentioning
confidence: 99%
“…Vol. 81,1986 light can be lower at low 02 concentrations could involve the operation of the mitochondrial alternative electron transport pathway (see [29] for a review) in the light. This nonphosphorylating, cyanide-resistant pathway is present (in addition to the phosphorylating, cyanide-sensitive Cyt pathway) in wheat and bean leaves (3,4), and it has been shown that the alternative pathway can operate in the dark under certain conditions in these leaves, and that the alternative pathway is apparently less restricted in vivo by oxidative phosphorylation than the Cyt pathway (4,5,22). If the activity of the alternative pathway increases in the light in leaves, which seems to be a feasible possibility because this pathway is less sensitive to adenylate energy charge (see above) and there is no substrate limitation (1, 3), then respiration in the light should be more sensitive to 02…”
mentioning
confidence: 99%
“…Triticum aestivum (cv Gabo) and Phaseolus vulgaris (cv Hawkesbury Wonder) plants were grown in a controlled environment in pots of soil. They were watered twice a day, and were fertilized every other day with nitrate-type Hewitt's solution (4). Total nitrate concentration was 12 mm.…”
mentioning
confidence: 99%